Tipologi Pronomina Persona dalam Bahasa Jawa, Sunda dan Madura - Menik Winiharti (Badan Pengembangan dan Pembinaan Bahasa, 2021)
One of the language typologies which can be observed in languages across the globe is personal pronouns. This paper aims to discover the characteristics of personal pronoun typology in three Indonesian local languages, namely Javanese, Sundanese and Madurese. It is also to find the similarities and differences of the three languages’ personal pronoun characteristics. The theory or claim used as the main reference is of Moravcsik (2013). The data are secondary ones which are personal pronouns in the three languages collected from textbooks and results of previous studies. The data is then identified with regard to each form, whether it is independent or not. If the pronoun is not independently formed, the process of its derivation is analyzed. The results of the study show that Javanese, Sundanese and Madurese have personal pronouns which are formed both independently and through a derivation process. The first personal pronouns tend to have an independent form while the second, third and plural personal pronouns tend to be formed through a derivation process. The most obvious difference is of the Javanese singular personal pronouns which do not have derivation in three speech levels.AbstrakSalah satu tipologi bahasa yang terdapat di semua bahasa di dunia adalah pronomina persona. Kajian ini bertujuan untuk mengetahui karakteristik tipologi pronomina persona dalam tiga bahasa daerah di Indonesia, yaitu bahasa Jawa, bahasa Sunda dan bahasa Madura, juga untuk mengetahui persamaan dan perbedaan karakteristik pronomina persona ketiga bahasa itu. Teori atau klaim yang digunakan sebagai rujukan utama adalah dari Moravcsik (2013). Data pronomina persona dalam ketiga bahasa tersebut berupa data sekunder yang diperoleh dari buku teks dan hasil studi terdahulu. Data ini kemudian diidentifikasi terkait masing-masing bentuknya, apakah independen atau tidak. Jika pronomina tersebut bukanlah bentuk yang independen, proses derivasinya dianalisis dan dirumuskan. Hasil studi menunjukkan bahwa bahasa Jawa, Sunda dan Madura memiliki bentuk pronomina persona baik yang independen maupun yang dibentuk melalui proses derivasi. Pronomina persona pertama cenderung memiliki bentuk yang independen sedangkan persona kedua, ketiga dan plural cenderung mengalami proses derivasi. Perbedaan yang jelas terlihat adalah pada pronomina persona tunggal bahasa Jawa yang tidak memiliki bentuk derivasi sama sekali pada tiga tingkatan tuturan.